Studies on B Cells in the Fruit-Eating Black Flying Fox (Pteropus alecto) - Periasamy, Pravin; Hutchinson, Paul E.; Chen, Jinmiao; Bonne, Isabelle; Shahul Hameed, Shahana Shereene; Selvam, Pavithra; Hey, Ying Ying; Fink, Katja; Irving, Aaron T.; Dutertre, Charles-Antoine; Baker, Michelle; Crameri, Gary; et al. (Frontiers in Immunology, 2019)
The ability of bats to act as reservoir for viruses that are highly pathogenic to humans suggests unique properties and functional characteristics of their immune system. However, the lack of bat specific reagents, in particular antibodies, has limited our knowledge of bat’s immunity. Here, we report a panel of cross-reactive antibodies against MHC-II, NK1.1, CD3, CD21, CD27, and immunoglobulin (Ig), that allows flow cytometry analysis of B, T and NK cell populations in two different fruit-eating bat species namely, P. alecto and E. spelaea. Results confirmed predominance of T cells in the spleen and blood of bats, as previously reported by us. However, the percentages of B cells in bone marrow and NK cells in spleen varied greatly between wild caught P. alecto bats and E. spelaea colony bats, which may reflect inherent differences of their immune system or different immune status. Other features of bat B cells were investigated. A significant increase in sIg+ B cell population was observed in the spleen and blood from LPS-injected bats but not from poly I:C-injected bats, supporting T-independent polyclonal B cell activation by LPS. Furthermore, using an in vitro calcium release assay, P. alecto B cells exhibited significant calcium release upon cross-linking of their B cell receptor. Together, this work contributes to improve our knowledge of bat adaptive immunity in particular B cells.